Faktor-Faktor Yang Mempengaruhi Penghindaran Pajak Pada Bank Perkreditan Rakyat Di Nusa Tenggara Timur. Factors Influencing Tax Avoidance In Rural Banks In East Nusa Tenggara - Lawa, Aginda Yunita; Anan, Edy; Andrianto, Wahyu (EBBANK, 2023)
This study aims to determine the effect of Leverage, Profitability, Company Size, Sales Growth on tax avoidance at Rural Banks in East Nusa Tenggara which are registered with the Financial Services Authority. This study uses the independent variables Leverage, Profitability, Company Size, Sales Growth while the dependent variable is Tax Avoidance. This study used a purposive sampling method. Data collection techniques using secondary data. Data were obtained from Rural Credit Banks in East Nusa Tenggara which were registered with the Financial Services Authority for the 2017-2021 semester using the Multiple Linear Regression method using the SPSS 23 application.The results of this study indicate that firm size has a significant positive effect on tax evasion. While the results are different from the variables Leverage, Profitability and Sales Growth have a positive and not significant effect on tax evasion. This research is expected to provide managerial implications regarding policies in acquiring assets which are a gap in tax avoidance practices because depreciation of assets can be a deduction from the tax burden and affect the level of banking income. The renewal of this research is the research object of BPRs in NTT which are registered with the OJK and the year used for the 2017-2021 period with the acquisition of semester data.